Prevalence and nature of survivorship needs in patients with head and neck cancer. Issue 7 (19th February 2016) - Giuliani, Meredith; McQuestion, Maurene; Jones, Jennifer; Papadakos, Janet; Le, Lisa W.; Alkazaz, Nour; Cheng, Terry; Waldron, John; Catton, Pamela; Ringash, Jolie
ABSTRACT: Background: The purpose of this study was to determine the number, type, and predictors of patients with head and neck cancer unmet survivorship needs. Methods: This study accrued patients with head and neck cancer at any time point in their survivorship course, and they completed a survey, including demographic information and the Cancer Survivors' Unmet Needs Measure (CaSUN). Results: The median age of the 158 participants was 64 years. Ninety‐six patients (61%) reported at least one unmet need on the CaSUN and 6 patients had a very high number of needs between 31 and 35. The mean number of unmet needs was 5.8 ± 8.9. Comprehensive Cancer Care was the most common domain of unmet need ( n = 69; 45%). Younger age, earlier survivorship phase, and worse quality of life were associated with increased survivorship unmet needs on multivariable analysis. Conclusion: A high proportion of patients with head and neck cancer have unmet needs. These data can guide the development of head and neck survivorship programs. © 2016 Wiley Periodicals, Inc. Head Neck 38: 1097–1103, 2016